Implementation of Internet Based Content Delivery Practices - Mali, Swati (Journal of Engineering Education Transformations, 2025)
The internet has taken education out of the conventional classrooms. The 21st century academicians believe in sharing their knowledge and embracing other’s ideas. The MOOC courses, use of ICT, collaborative learning are some of the methods being followed by academicians around the world and they are also very much appreciated by students of current generations. This paper discusses implementation of few Internets based teaching-learning approaches which could be used in schools and colleges for any subject. The methods aim at students’ engagement and effective education.